Distribution of tyrosol fatty acid esters in the gastrointestinal tracts of mice and their hydrolysis characteristics by gut microbiota. Issue 5 (23rd February 2022) - Wang, Xinmiao; Chen, Kefan; Wang, Sijia; Wang, Qian; Hu, Yuanyuan; Yin, Fawen; Liu, Xiaoyang; Zhou, Dayong
Abstract : Phenolic lipids have been approved as safe and effective antioxidants, and are a potential ingredient for functional foods. Abstract : Phenolic lipids have been approved as safe and effective antioxidants, and are a potential ingredient for functional foods. However, the characteristics of gastrointestinal distribution and microbial hydrolysis in the gastrointestinal tract (GI) are not clear. In this study, the above characteristics of tyrosol-myristic acid ester (T-C14:0), tyrosol-palmitic acid ester (T-C16:0) and tyrosol-stearic acid ester (T-C18:0) were estimated by an in vivo mice model and in vitro anaerobic fermentation model. HPLC-UV measurements indicate that tyrosol (TYr) was rapidly and almost completely absorbed in the small intestine. By contrast, oral T-C14:0, T-C16:0 and T-C18:0 were remarkably stable in the stomach environments of the mice, and could be further hydrolyzed to free TYr by gut microbiota including Lactobacillus johnsonii, Lactobacillus reuteri and Lactobacillus gasseri (in the colon and cecum). Further, the liberated TYr and fatty acids can participate in regulating the composition of the gut microorganisms, which may lead to some additional health benefits. Therefore, the production of phenolic lipids such as tyrosol fatty acid esters provides a new approach to prolong the action time of polyphenol in vivo, and could also lead to additional health benefits including the regulation of gut microorganisms.